Aqueous zinc ion battery electrolyte, preparation method and application thereof

By using potassium gluconate and dimethyl sulfoxide as additives in zinc-ion batteries, the solvation structure of zinc ions was adjusted, solving the problems of zinc dendrite growth and hydrogen evolution reaction, improving battery stability and lifespan, and enhancing battery performance.

CN120999147APending Publication Date: 2025-11-21CHENGDU UNIV OF INFORMATION TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510918207.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-03
Publication Date
2025-11-21

AI Technical Summary

Technical Problem

Zinc dendrite growth and hydrogen evolution reaction lead to uneven charging and discharging of zinc-ion batteries, affecting battery stability and lifespan. Furthermore, the reaction of metallic zinc with water to generate hydrogen gas corrodes the negative electrode, reducing battery performance.

Method used

An aqueous zinc-ion battery electrolyte containing potassium gluconate and dimethyl sulfoxide is used. The solvation process of zinc ions is carried out through the participation of carboxyl, hydroxyl and sulfoxide groups, which adjust the solvation structure, form a stable electrolyte interface, and inhibit dendrite growth and hydrogen evolution reaction.

Benefits of technology

It improves the coulombic efficiency and cycle stability of zinc-ion batteries, suppresses side reactions, extends battery life and enhances conductivity, and the preparation process is simple and environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120999147A_ABST
    Figure CN120999147A_ABST
Patent Text Reader

Abstract

The invention discloses an aqueous zinc ion battery electrolyte. The aqueous zinc ion battery electrolyte comprises soluble zinc salt, a solvent and an additive, the additives are potassium gluconate and dimethyl sulfoxide, the concentration of the potassium gluconate is 0.05 mol / L to 0.2 mol / L, and the concentration of the dimethyl sulfoxide is 5 v% to 10 v%. The electrolyte effectively solves the problems of zinc dendrite growth, hydrogen evolution reaction, zinc corrosion and the like of the aqueous zinc ion battery, and greatly improves the cycle reversibility and interface stability of the aqueous zinc ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of aqueous zinc-ion battery technology, and more specifically, relates to an aqueous zinc-ion battery electrolyte, its preparation method, and its application. Background Technology

[0002] With the rapid development of modern society, human demand for energy is constantly increasing, and the requirements for energy storage devices are also becoming more stringent. Due to its advantages such as fast ion transport kinetics, high energy density, environmental friendliness, low cost, and high safety, aqueous zinc-ion batteries are considered to be energy storage devices with great development potential. The components of a zinc-ion battery generally include a zinc negative electrode, a redox positive electrode, a glass fiber separator, and a neutral or weakly acidic electrolyte.

[0003] Its working principle is that during the discharge process, zinc first undergoes an oxidation reaction to generate Zn. 2+ Upon entering the electrolyte, the zinc is transported to the positive electrode and embedded within the positive electrode material. Simultaneously, electrons transferred from the external circuit are reduced at the positive electrode. The charging process is the exact opposite. However, during charging and discharging, the zinc plating / stripping process of zinc-ion batteries is often uneven. This leads to irregular surface appearance and zinc dendrite growth that punctures the separator, causing short-circuit failures. Furthermore, metallic zinc spontaneously reacts with water in the electrolyte to form Zn. 2+ The presence of hydrogen and H2 leads to hydrogen evolution and corrosion on the zinc anode, which poses a significant threat to coulombic efficiency (CE) and long-term cycle stability, severely reducing battery life and electrochemical performance. Summary of the Invention

[0004] To address at least one defect or improvement requirement in the prior art, this invention provides an aqueous zinc-ion battery electrolyte that can suppress problems such as zinc dendrite growth and hydrogen evolution reaction. This electrolyte contains carboxyl, hydroxyl, and sulfoxide groups, which participate in the solvation process of zinc ions, thereby adjusting the solvation structure of zinc ions in aqueous solution, suppressing side reactions such as hydrogen evolution corrosion, and exhibiting excellent zinc affinity to induce a uniform zinc ion flux, preventing dendrite formation, and improving the stability and cycle life of the zinc-ion battery.

[0005] To achieve the above objectives, according to one aspect of the present invention, an aqueous zinc-ion battery electrolyte is provided, comprising: a soluble zinc salt, a solvent, and an additive; wherein the additive is potassium gluconate and dimethyl sulfoxide, the concentration of potassium gluconate is 0.05–0.2 mol / L, and the concentration of dimethyl sulfoxide is 5–10 vol.

[0006] Furthermore, the concentration of the soluble zinc salt is 1–3 mol / L.

[0007] Furthermore, the soluble zinc salt electrolyte is one or more of zinc sulfate, zinc chloride, zinc acetate, zinc perchlorate, zinc nitrate, and zinc trifluoromethanesulfonate.

[0008] Furthermore, the solvent is deionized water.

[0009] According to a second aspect of the present invention, a method for preparing an aqueous zinc-ion battery electrolyte is also provided, comprising the following steps: A. Add soluble zinc salt to deionized water and stir to dissolve, thus obtaining the basic electrolyte; B. Add potassium gluconate to the basic electrolyte and stir to dissolve. The concentration of potassium gluconate is 0.05-0.2 mol / L. C. Add dimethyl sulfoxide and stir to mix well to obtain the product. The concentration of dimethyl sulfoxide is 5-10 v.

[0010] According to a third aspect of the present invention, an aqueous zinc-ion battery is also provided, comprising a positive electrode, a negative electrode, an electrolyte, and a separator disposed between the positive electrode and the negative electrode, wherein the electrolyte is the aqueous zinc-ion battery electrolyte according to any one of claims 1-3.

[0011] Furthermore, the positive electrode is made of copper, zinc, or a zinc alloy.

[0012] Furthermore, the negative electrode is made of zinc or a zinc alloy material.

[0013] Furthermore, the positive electrode is formed by coating the current collector with one of the following active materials: a vanadium-based compound, a manganese-based compound, and a Prussian blue-like compound.

[0014] Furthermore, the current collector can be any one of stainless steel mesh, carbon paper, carbon cloth, and graphite paper.

[0015] According to a fourth aspect of the present invention, the application of the aqueous zinc-ion battery electrolyte and the method for preparing the electrolyte described in any of the preceding claims in an aqueous zinc-ion battery is also provided.

[0016] In summary, compared with the prior art, the above-described technical solutions conceived by this invention can achieve the following beneficial effects: (1) The present invention provides an aqueous zinc-ion battery electrolyte, preparation method and application, which uses a certain proportion of potassium gluconate and dimethyl sulfoxide as additives added to the electrolyte. The carboxyl, hydroxyl and sulfoxide groups of the additives participate in the solvation process of zinc ions, thereby adjusting the solvation structure of zinc ions in aqueous solution. Among them, the carboxyl and hydroxyl groups of potassium gluconate form hydrogen bonds with water molecules, thereby improving the solubility of zinc ions. Secondly, the carboxyl, hydroxyl and sulfoxide groups can form a stable electrolyte interface during the charging and discharging process of zinc-ion battery, reduce the side reactions on the zinc electrode surface, thereby helping to increase the ion concentration in the electrolyte and improve the conductivity of the electrolyte. Compared with the battery prepared without the addition of potassium gluconate and dimethyl sulfoxide, its coulombic efficiency and cycle stability are greatly improved.

[0017] (2) The aqueous zinc-ion battery electrolyte, preparation method and application provided by the present invention can suppress side reactions such as hydrogen evolution corrosion, and the good zinc affinity induces uniform zinc ion flux, thereby avoiding the generation of dendrites, increasing the protection of the aqueous zinc-ion zinc anode, and improving the stability and cycle life of zinc-ion batteries.

[0018] (3) The aqueous zinc-ion battery electrolyte, preparation method and application provided by the present invention are simple to prepare, low in cost and safe and environmentally friendly. Attached Figure Description

[0019] Figure 1 The Zn||Zn symmetric cells prepared with the electrolytes of Examples 1-12 of this invention are shown at a current density of 1 mA / cm². -2 The current capacity is 1mAh cm⁻¹ -2 Cyclic performance graph under the given conditions; Figure 2 The Zn||Cu battery prepared with the electrolyte of Examples 1-12 of this invention operates at a current density of 1 mA cm⁻¹. -2 The current capacity is 1mAh cm⁻¹ -2 Cyclic performance graph under the given conditions; Figure 3 This is a cycle performance graph of the Zn||V₂O₅ full cells prepared in Example 13 and Comparative Example 1 of this invention under a current density of 1 A / g. Figure 4 These are the cycle performance diagrams of Zn||Zn symmetric batteries in Embodiment 8 and Comparative Example 1 of the present invention; Figure 5 This is a coulombic efficiency diagram of a Zn||Cu battery in Example 8 and Comparative Example 1 of the present invention. Figure 6 The LSV curves obtained from tests in Example 8 and Comparative Example 1 are shown. Figure 7The images show SEM images of Zn foil after immersion in the electrolyte of Example 8 and Comparative Example 1 for 8 days. Detailed Implementation

[0020] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention. Furthermore, the technical features involved in the various embodiments of this invention described below can be combined with each other as long as they do not conflict with each other.

[0021] In the description of this invention, it should be understood that the terms "center," "longitudinal," "lateral," "length," "width," "thickness," "upper," "lower," "front," "rear," "left," "right," "vertical," "horizontal," "top," "bottom," "inner," "outer," "clockwise," "counterclockwise," "axial," "radial," and "circumferential" indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings. They are used only for the convenience of describing this invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, they should not be construed as limitations on this invention.

[0022] Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of that feature. In the description of this invention, "a plurality of" means at least two, such as two, three, etc., unless otherwise explicitly specified.

[0023] In this invention, unless otherwise explicitly specified and limited, the terms "installation," "connection," "linking," and "fixing," etc., should be interpreted broadly. For example, they can refer to a fixed connection, a detachable connection, or an integral part; they can refer to a mechanical connection or an electrical connection; they can refer to a direct connection or an indirect connection through an intermediate medium; they can refer to the internal communication of two components or the interaction between two components, unless otherwise explicitly limited. Those skilled in the art can understand the specific meaning of the above terms in this invention according to the specific circumstances.

[0024] In this invention, unless otherwise explicitly specified and limited, "above" or "below" the second feature can mean that the first feature is in direct contact with the second feature, or that the first feature is in indirect contact with the second feature through an intermediate medium. Furthermore, "above," "over," and "on top" of the second feature can mean that the first feature is directly above or diagonally above the second feature, or simply that the first feature is at a higher horizontal level than the second feature. "Below," "below," and "under" the second feature can mean that the first feature is directly below or diagonally below the second feature, or simply that the first feature is at a lower horizontal level than the second feature.

[0025] Unless otherwise specified, all materials and reagents used in the following examples were obtained commercially.

[0026] The chemical symbols and corresponding meanings of the compounds used in this invention are as follows: The following specific embodiments further illustrate the aqueous zinc-ion battery electrolyte, its preparation method, and its application provided by the present invention.

[0027] Example 1 A method for preparing an aqueous zinc-ion battery electrolyte includes the following steps: (1) Weigh 2.8756g of solid ZnSO4·7H2O and add it to an empty beaker. Add deionized water to the beaker and make up to 5ml. Stir thoroughly at 25℃ until completely dissolved to obtain a ZnSO4 solution with a concentration of 2mol / L.

[0028] (2) Weigh 58.56 mg of potassium gluconate powder and add it to the ZnSO4 solution obtained in (1). Stir thoroughly at 25°C for 2 hours until completely dissolved to obtain a potassium gluconate modified electrolyte with a concentration of 0.05 mol / L, denoted as ZnSO4+KG0.05.

[0029] (3) Take 4.75 ml of the ZnSO4+KG0.05 solution obtained in (2) and add 0.25 ml of dimethyl sulfoxide solution with a pipette. Stir thoroughly at 25°C for 2 h to obtain a dimethyl sulfoxide modified electrolyte with a volume ratio of 10 v%, which is denoted as ZnSO4+KG0.05+DMSO5.

[0030] ① A button-type Zn||Zn symmetric battery of model CR2016 was assembled using zinc foil (thickness of 30μm) as positive and negative electrodes, glass fiber as separator, and the above electrolyte.

[0031] The button cell was tested using the Xinwei multi-channel battery testing system. The Zn||Zn symmetric cell in this comparative example was tested at a current density of 1 mA cm⁻¹. -2 Discharge capacity is 1mAh cm-2 Cyclic performance testing under the following conditions, such as Figure 1 As shown in (a).

[0032] ② A button-type Zn||Cu half-cell was assembled using zinc foil (30μm thick) as the negative electrode, copper foil (30μm thick) as the positive electrode, glass fiber as the separator, and the above electrolyte.

[0033] The button cell was tested using the Xinwei multi-channel battery testing system. In this embodiment, the Zn||Cu half-cell was tested at a current density of 1 mA cm⁻¹. -2 Discharge capacity is 1mAh cm -2 Coulomb efficiency under the condition as Figure 2 As shown in (a), the stable cycle is 50 times.

[0034] Example 2 An aqueous zinc-ion battery electrolyte with potassium gluconate and dimethyl sulfoxide as additives, its preparation method and application, comprising the following steps: (1) Weigh 2.8756g of solid ZnSO4·7H2O and add it to an empty beaker. Add deionized water to the beaker and make up to 5ml. Stir thoroughly at 25℃ until completely dissolved to obtain a ZnSO4 solution with a concentration of 2mol / L.

[0035] (2) Weigh 58.56 mg of potassium gluconate powder and add it to the ZnSO4 solution obtained in (1). Stir thoroughly at 25°C for 2 hours until completely dissolved to obtain a potassium gluconate modified electrolyte with a concentration of 0.05 mol / L, denoted as ZnSO4+KG0.05.

[0036] (3) Take 4.5 ml of the ZnSO4+KG0.05 solution obtained in (2) and add 0.5 ml of dimethyl sulfoxide solution with a pipette. Stir thoroughly at 25°C for 2 h to obtain a dimethyl sulfoxide modified electrolyte with a volume ratio of 10 v%, which is denoted as ZnSO4+KG0.05+DMSO10.

[0037] ① A button-type Zn||Zn symmetric battery of model CR2016 was assembled using zinc foil (30 μm thick) as the positive and negative electrodes, glass fiber as the separator, and the above electrolyte.

[0038] The button cell was tested using the Xinwei multi-channel battery testing system. The Zn||Zn symmetric cell in this comparative example was tested at a current density of 1 mA cm⁻¹. -2 Discharge capacity is 1mAh cm -2 Cyclic performance testing under the following conditions, such as Figure 1 As shown in (a).

[0039] ② A button-type Zn||Cu half-cell was assembled using zinc foil (30 μm thick) as the negative electrode, copper foil (30 μm thick) as the positive electrode, glass fiber as the separator, and the above electrolyte.

[0040] The button cell was tested using the Xinwei multi-channel battery testing system. In this embodiment, the Zn||Cu half-cell was tested at a current density of 1 mA cm⁻¹. -2 Discharge capacity is 1mAh cm -2 Coulomb efficiency under the condition as Figure 2 As shown in (a), the stable cycle is 50 times.

[0041] Example 3 An aqueous zinc-ion battery electrolyte with potassium gluconate and dimethyl sulfoxide as additives, its preparation method and application, comprising the following steps: (1) Weigh 2.8756g of solid ZnSO4·7H2O and add it to an empty beaker. Add deionized water to the beaker and make up to 5ml. Stir thoroughly at 25℃ until completely dissolved to obtain a ZnSO4 solution with a concentration of 2mol / L.

[0042] (2) Weigh 58.56 mg of potassium gluconate powder and add it to the ZnSO4 solution obtained in (1). Stir thoroughly at 25°C for 2 hours until completely dissolved to obtain a potassium gluconate modified electrolyte with a concentration of 0.05 mol / L, denoted as ZnSO4+KG0.05.

[0043] (3) Take 4.25 ml of the ZnSO4+KG0.05 solution obtained in (2) and add 0.75 ml of dimethyl sulfoxide solution with a pipette. Stir thoroughly at 25°C for 2 h to obtain a dimethyl sulfoxide modified electrolyte with a volume ratio of 15v%, which is denoted as ZnSO4+KG0.05+DMSO15.

[0044] ① A button-type Zn||Zn symmetric battery of model CR2016 was assembled using zinc foil (30 μm thick) as the positive and negative electrodes, glass fiber as the separator, and the above electrolyte.

[0045] The button cell was tested using the Xinwei multi-channel battery testing system. The Zn||Zn symmetric cell in this comparative example was tested at a current density of 1 mA cm⁻¹. -2 Discharge capacity is 1mAh cm -2 Cyclic performance testing under the following conditions, such as Figure 1 As shown in (a).

[0046] ② A button-type Zn||Cu half-cell was assembled using zinc foil (30μm thick) as the negative electrode, copper foil (30μm thick) as the positive electrode, glass fiber as the separator, and the above electrolyte.

[0047] The button cell was tested using the Xinwei multi-channel battery testing system. In this embodiment, the Zn||Cu half-cell was tested at a current density of 1 mA cm⁻¹. -2 Discharge capacity is 1mAh cm -2 Coulomb efficiency under the condition as Figure 2 As shown in (a), the stable cycle lasts for 85 cycles.

[0048] Example 4 An aqueous zinc-ion battery electrolyte with potassium gluconate and dimethyl sulfoxide as additives, its preparation method and application, comprising the following steps: (1) Weigh 2.8756g of solid ZnSO4·7H2O and add it to an empty beaker. Add deionized water to the beaker and make up to 5ml. Stir thoroughly at 25℃ until completely dissolved to obtain a ZnSO4 solution with a concentration of 2mol / L.

[0049] (2) Weigh 117.13 mg of potassium gluconate powder and add it to the ZnSO4 solution obtained in (1). Stir it thoroughly at 25°C for 2 hours until it is completely dissolved to obtain a potassium gluconate modified electrolyte with a concentration of 0.1 mol / L, which is denoted as ZnSO4+KG0.1.

[0050] (3) Take 4.75 ml of the ZnSO4+KG0.1 solution obtained in (2) and add 0.25 ml of dimethyl sulfoxide solution with a pipette. Stir thoroughly at 25°C for 2 h to obtain a dimethyl sulfoxide modified electrolyte with a volume ratio of 5v%, which is denoted as ZnSO4+KG0.1+DMSO5.

[0051] ① A button-type Zn||Zn symmetric battery of model CR2016 was assembled using zinc foil (30 μm thick) as the positive and negative electrodes, glass fiber as the separator, and the above electrolyte.

[0052] The button cell was tested using the Xinwei multi-channel battery testing system. The Zn||Zn symmetric cell in this comparative example was tested at a current density of 1 mA cm⁻¹. -2 Discharge capacity is 1mAh cm -2 Cyclic performance testing under the following conditions, such as Figure 1 As shown in (b).

[0053] ② A button-type Zn||Cu half-cell was assembled using zinc foil (30 μm thick) as the negative electrode, copper foil (30 μm thick) as the positive electrode, glass fiber as the separator, and the above electrolyte.

[0054] The button cell was tested using the Xinwei multi-channel battery testing system. In this embodiment, the Zn||Cu half-cell was tested at a current density of 1 mA cm⁻¹. -2 Discharge capacity is 1mAh cm -2 Coulomb efficiency under the condition as Figure 2 As shown in (b), the stable cycle lasts for 75 cycles.

[0055] Example 5 An aqueous zinc-ion battery electrolyte with potassium gluconate and dimethyl sulfoxide as additives, its preparation method and application, comprising the following steps: (1) Weigh 2.8756g of solid ZnSO4·7H2O and add it to an empty beaker. Add deionized water to the beaker and make up to 5ml. Stir thoroughly at 25℃ until completely dissolved to obtain a ZnSO4 solution with a concentration of 2mol / L.

[0056] (2) Weigh 117.13 mg of potassium gluconate powder and add it to the ZnSO4 solution obtained in (1). Stir it thoroughly at 25°C for 2 hours until it is completely dissolved to obtain a potassium gluconate modified electrolyte with a concentration of 0.1 mol / L, which is denoted as ZnSO4+KG0.1.

[0057] (3) Take 4.5 ml of the ZnSO4+KG0.1 solution obtained in (2) and add 0.5 ml of dimethyl sulfoxide solution with a pipette. Stir thoroughly at 25°C for 2 h to obtain a dimethyl sulfoxide modified electrolyte with a volume ratio of 10 v%, which is denoted as ZnSO4+KG0.1+DMSO10.

[0058] ① A button-type Zn||Zn symmetric battery of model CR2016 was assembled using zinc foil (30 μm thick) as the positive and negative electrodes, glass fiber as the separator, and the above electrolyte.

[0059] The button cell was tested using the Xinwei multi-channel battery testing system. The Zn||Zn symmetric cell in this comparative example was tested at a current density of 1 mA cm⁻¹. -2 Discharge capacity is 1mAh cm -2 Cyclic performance testing under the following conditions, such as Figure 1 As shown in (b).

[0060] ② A button-type Zn||Cu half-cell was assembled using zinc foil (30μm thick) as the negative electrode, copper foil (30μm thick) as the positive electrode, glass fiber as the separator, and the above electrolyte.

[0061] The button cell was tested using the Xinwei multi-channel battery testing system. In this embodiment, the Zn||Cu half-cell was tested at a current density of 1 mA cm⁻¹. -2 Discharge capacity is 1mAh cm -2 Coulomb efficiency under the condition as Figure 2 As shown in (b), the stable cycle is 175 times.

[0062] Example 6 An aqueous zinc-ion battery electrolyte with potassium gluconate and dimethyl sulfoxide as additives, its preparation method and application, comprising the following steps: (1) Weigh 2.8756g of solid ZnSO4·7H2O and add it to an empty beaker. Add deionized water to the beaker and make up to 5ml. Stir thoroughly at 25℃ until completely dissolved to obtain a ZnSO4 solution with a concentration of 2mol / L.

[0063] (2) Weigh 117.13 mg of potassium gluconate powder and add it to the ZnSO4 solution obtained in (1). Stir it thoroughly at 25°C for 2 hours until it is completely dissolved to obtain a potassium gluconate modified electrolyte with a concentration of 0.1 mol / L, which is denoted as ZnSO4+KG0.1.

[0064] (3) Take 4.25 ml of the ZnSO4+KG0.1 solution obtained in (2) and add 0.75 ml of dimethyl sulfoxide solution with a pipette. Stir thoroughly at 25°C for 2 h to obtain a dimethyl sulfoxide modified electrolyte with a volume ratio of 15v%, which is denoted as ZnSO4+KG0.1+DMSO15.

[0065] ① A button-type Zn||Zn symmetric battery of model CR2016 was assembled using zinc foil (30 μm thick) as the positive and negative electrodes, glass fiber as the separator, and the above electrolyte.

[0066] The button cell was tested using the Xinwei multi-channel battery testing system. The Zn||Zn symmetric cell in this comparative example was tested at a current density of 1 mA cm⁻¹. -2 Discharge capacity is 1mAh cm -2 Cyclic performance testing under the following conditions, such as Figure 1 As shown in (b).

[0067] ② A button-type Zn||Cu half-cell was assembled using zinc foil (30μm thick) as the negative electrode, copper foil (30μm thick) as the positive electrode, glass fiber as the separator, and the above electrolyte.

[0068] The button cell was tested using the Xinwei multi-channel battery testing system. In this embodiment, the Zn||Cu half-cell was tested at a current density of 1 mA cm⁻¹. -2 Discharge capacity is 1mAh cm -2 Coulomb efficiency under the condition as Figure 2 As shown in (b), the stable cycle is 150 times.

[0069] Example 7 An aqueous zinc-ion battery electrolyte with potassium gluconate and dimethyl sulfoxide as additives, its preparation method and application, comprising the following steps: (1) Weigh 2.8756g of solid ZnSO4·7H2O and add it to an empty beaker. Add deionized water to the beaker and make up to 5ml. Stir thoroughly at 25℃ until completely dissolved to obtain a ZnSO4 solution with a concentration of 2mol / L.

[0070] (2) Weigh 175.69 mg of potassium gluconate powder and add it to the ZnSO4 solution obtained in (1). Stir thoroughly at 25°C for 2 hours until completely dissolved to obtain a potassium gluconate modified electrolyte with a concentration of 0.15 mol / L, denoted as ZnSO4+KG0.15.

[0071] (3) Take 4.75 ml of the ZnSO4+KG0.15 solution obtained in (2) and add 0.25 ml of dimethyl sulfoxide solution with a pipette. Stir thoroughly at 25°C for 2 h to obtain a dimethyl sulfoxide modified electrolyte with a volume ratio of 5 v%, which is denoted as ZnSO4+KG0.15+DMSO5.

[0072] ① A button-type Zn||Zn symmetric battery of model CR2016 was assembled using zinc foil (30 μm thick) as the positive and negative electrodes, glass fiber as the separator, and the above electrolyte.

[0073] The button cell was tested using the Xinwei multi-channel battery testing system. The Zn||Zn symmetric cell in this comparative example was tested at a current density of 1 mA cm⁻¹. -2 Discharge capacity is 1mAh cm -2 Cyclic performance testing under the following conditions, such as Figure 1 As shown in (c).

[0074] ② A button-type Zn||Cu half-cell was assembled using zinc foil (30μm thick) as the negative electrode, copper foil (30μm thick) as the positive electrode, glass fiber as the separator, and the above electrolyte.

[0075] The button cell was tested using the Xinwei multi-channel battery testing system. In this embodiment, the Zn||Cu half-cell was tested at a current density of 1 mA cm⁻¹. -2 Discharge capacity is 1mAh cm -2 Coulomb efficiency under the condition as Figure 2 As shown in (c), the stable cycle is 120 times.

[0076] Example 8 An aqueous zinc-ion battery electrolyte with potassium gluconate and dimethyl sulfoxide as additives, its preparation method and application, comprising the following steps: (1) Weigh 2.8756g of solid ZnSO4·7H2O and add it to an empty beaker. Add deionized water to the beaker and make up to 5ml. Stir thoroughly at 25℃ until completely dissolved to obtain a ZnSO4 solution with a concentration of 2mol / L.

[0077] (2) Weigh 175.69 mg of potassium gluconate powder and add it to the ZnSO4 solution obtained in (1). Stir thoroughly at 25°C for 2 hours until completely dissolved to obtain a potassium gluconate modified electrolyte with a concentration of 0.15 mol / L, denoted as ZnSO4+KG0.15.

[0078] (3) Take 4.5 ml of the ZnSO4+KG0.15 solution obtained in (2) and add 0.5 ml of dimethyl sulfoxide solution with a pipette. Stir thoroughly at 25°C for 2 h to obtain a dimethyl sulfoxide modified electrolyte with a volume ratio of 10 v%, which is denoted as ZnSO4+KG0.15+DMSO10.

[0079] ① A button-type Zn||Zn symmetric battery of model CR2016 was assembled using zinc foil (30 μm thick) as the positive and negative electrodes, glass fiber as the separator, and the above electrolyte.

[0080] The button cell was tested using the Xinwei multi-channel battery testing system. The Zn||Zn symmetric cell in this comparative example was tested at a current density of 1 mA cm⁻¹. -2 Discharge capacity is 1mAh cm -2 Cyclic performance testing under the following conditions, such as Figure 1 As shown in (c).

[0081] ② A button-type Zn||Cu half-cell was assembled using zinc foil (30μm thick) as the negative electrode, copper foil (30μm thick) as the positive electrode, glass fiber as the separator, and the above electrolyte.

[0082] The button cell was tested using the Xinwei multi-channel battery testing system. In this embodiment, the Zn||Cu half-cell was tested at a current density of 1 mA cm⁻¹. -2 Discharge capacity is 1mAh cm -2 Coulomb efficiency under the condition as Figure 2 As shown in (c), the stable cycle is 257 times.

[0083] Example 9 An aqueous zinc-ion battery electrolyte with potassium gluconate and dimethyl sulfoxide as additives, its preparation method and application, comprising the following steps: (1) Weigh 2.8756g of solid ZnSO4·7H2O and add it to an empty beaker. Add deionized water to the beaker and make up to 5ml. Stir thoroughly at 25℃ until completely dissolved to obtain a ZnSO4 solution with a concentration of 2mol / L.

[0084] (2) Weigh 175.69 mg of potassium gluconate powder and add it to the ZnSO4 solution obtained in (1). Stir thoroughly at 25°C for 2 hours until completely dissolved to obtain a potassium gluconate modified electrolyte with a concentration of 0.15 mol / L, denoted as ZnSO4+KG0.15.

[0085] (3) Take 4.25 ml of the ZnSO4+KG0.15 solution obtained in (2) and add 0.75 ml of dimethyl sulfoxide solution with a pipette. Stir thoroughly at 25°C for 2 h to obtain a dimethyl sulfoxide modified electrolyte with a volume ratio of 15v%, which is denoted as ZnSO4+KG0.15+DMSO15.

[0086] ① A button-type Zn||Zn symmetric battery of model CR2016 was assembled using zinc foil (30 μm thick) as the positive and negative electrodes, glass fiber as the separator, and the above electrolyte.

[0087] The button cell was tested using the Xinwei multi-channel battery testing system. The Zn||Zn symmetric cell in this comparative example was tested at a current density of 1 mA cm⁻¹. -2 Discharge capacity is 1mAh cm -2 Cyclic performance testing under the following conditions, such as Figure 1 As shown in (c).

[0088] ② A button-type Zn||Cu half-cell was assembled using zinc foil (30μm thick) as the negative electrode, copper foil (30μm thick) as the positive electrode, glass fiber as the separator, and the above electrolyte.

[0089] The button cell was tested using the Xinwei multi-channel battery testing system. In this embodiment, the Zn||Cu half-cell was tested at a current density of 1 mA cm⁻¹. -2 Discharge capacity is 1mAh cm -2 Coulomb efficiency under the condition as Figure 2 As shown in (c), the stable cycle is 50 times.

[0090] Example 10 An aqueous zinc-ion battery electrolyte with potassium gluconate and dimethyl sulfoxide as additives, its preparation method and application, comprising the following steps: (1) Weigh 2.8756g of solid ZnSO4·7H2O and add it to an empty beaker. Add deionized water to the beaker and make up to 5ml. Stir thoroughly at 25℃ until completely dissolved to obtain a ZnSO4 solution with a concentration of 2mol / L.

[0091] (2) Weigh 234.25 mg of potassium gluconate powder and add it to the ZnSO4 solution obtained in (1). Stir thoroughly at 25°C for 2 hours until completely dissolved to obtain a potassium gluconate modified electrolyte with a concentration of 0.2 mol / L, denoted as ZnSO4+KG0.2.

[0092] (3) Take 4.75 ml of the ZnSO4+KG0.2 solution obtained in (2) and add 0.25 ml of dimethyl sulfoxide solution with a pipette. Stir thoroughly at 25°C for 2 h to obtain a dimethyl sulfoxide modified electrolyte with a volume ratio of 5v%, which is denoted as ZnSO4+KG0.2+DMSO5.

[0093] ① A button-type Zn||Zn symmetric battery of model CR2016 was assembled using zinc foil (30 μm thick) as the positive and negative electrodes, glass fiber as the separator, and the above electrolyte.

[0094] The button cell was tested using the Xinwei multi-channel battery testing system. The Zn||Zn symmetric cell in this comparative example was tested at a current density of 1 mA cm⁻¹. -2 Discharge capacity is 1mAh cm -2 Cyclic performance testing under the following conditions, such as Figure 1 As shown in (d).

[0095] ② A button-type Zn||Cu half-cell was assembled using zinc foil (30μm thick) as the negative electrode, copper foil (30μm thick) as the positive electrode, glass fiber as the separator, and the above electrolyte.

[0096] The button cell was tested using the Xinwei multi-channel battery testing system. In this embodiment, the Zn||Cu half-cell was tested at a current density of 1 mA cm⁻¹. -2 Discharge capacity is 1mAh cm -2 Coulomb efficiency under the condition as Figure 2 As shown in (d), the stable cycle lasts for 75 revolutions.

[0097] Example 11 An aqueous zinc-ion battery electrolyte with potassium gluconate and dimethyl sulfoxide as additives, its preparation method and application, comprising the following steps: (1) Weigh 2.8756g of solid ZnSO4·7H2O and add it to an empty beaker. Add deionized water to the beaker and make up to 5ml. Stir thoroughly at 25℃ until completely dissolved to obtain a ZnSO4 solution with a concentration of 2mol / L.

[0098] (2) Weigh 234.25 mg of potassium gluconate powder and add it to the ZnSO4 solution obtained in (1). Stir thoroughly at 25°C for 2 hours until completely dissolved to obtain a potassium gluconate modified electrolyte with a concentration of 0.2 mol / L, denoted as ZnSO4+KG0.2.

[0099] (3) Take 4.5 ml of the ZnSO4+KG0.2 solution obtained in (2) and add 0.5 ml of dimethyl sulfoxide solution with a pipette. Stir thoroughly at 25°C for 2 h to obtain a dimethyl sulfoxide modified electrolyte with a volume ratio of 10 v%, which is denoted as ZnSO4+KG0.2+DMSO10.

[0100] ① A button-type Zn||Zn symmetric battery of model CR2016 was assembled using zinc foil (30 μm thick) as the positive and negative electrodes, glass fiber as the separator, and the above electrolyte.

[0101] The button cell was tested using the Xinwei multi-channel battery testing system. The Zn||Zn symmetric cell in this comparative example was tested at a current density of 1 mA cm⁻¹. -2 Discharge capacity is 1mAh cm -2 Cyclic performance testing under the following conditions, such as Figure 1 As shown in (d).

[0102] ② A button-type Zn||Cu half-cell was assembled using zinc foil (30μm thick) as the negative electrode, copper foil (30μm thick) as the positive electrode, glass fiber as the separator, and the above electrolyte.

[0103] The button cell was tested using the Xinwei multi-channel battery testing system. In this embodiment, the Zn||Cu half-cell was tested at a current density of 1 mA cm⁻¹.-2 Discharge capacity is 1mAh cm -2 Coulomb efficiency under the condition as Figure 2 As shown in (d), the stable cycle is 160 times.

[0104] Example 12 An aqueous zinc-ion battery electrolyte with potassium gluconate and dimethyl sulfoxide as additives, its preparation method and application, comprising the following steps: (1) Weigh 2.8756g of solid ZnSO4·7H2O and add it to an empty beaker. Add deionized water to the beaker and make up to 5ml. Stir thoroughly at 25℃ until completely dissolved to obtain a ZnSO4 solution with a concentration of 2mol / L.

[0105] (2) Weigh 234.25 mg of potassium gluconate powder and add it to the ZnSO4 solution obtained in (1). Stir thoroughly at 25°C for 2 hours until completely dissolved to obtain a potassium gluconate modified electrolyte with a concentration of 0.2 mol / L, denoted as ZnSO4+KG0.2.

[0106] (3) Take 4.25 ml of the ZnSO4+KG0.2 solution obtained in (2) and add 0.75 ml of dimethyl sulfoxide solution with a pipette. Stir thoroughly at 25°C for 2 h to obtain a dimethyl sulfoxide modified electrolyte with a volume ratio of 15v%, which is denoted as ZnSO4+KG0.2+DMSO15.

[0107] ① A button-type Zn||Zn symmetric battery of model CR2016 was assembled using zinc foil (30 μm thick) as the positive and negative electrodes, glass fiber as the separator, and the above electrolyte.

[0108] The button cell was tested using the Xinwei multi-channel battery testing system. The Zn||Zn symmetric cell in this comparative example was tested at a current density of 1 mA cm⁻¹. -2 Discharge capacity is 1mAh cm -2 Cyclic performance testing under the following conditions, such as Figure 1 As shown in (d).

[0109] ② A button-type Zn||Cu half-cell was assembled using zinc foil (30μm thick) as the negative electrode, copper foil (30μm thick) as the positive electrode, glass fiber as the separator, and the above electrolyte.

[0110] The button cell was tested using the Xinwei multi-channel battery testing system. In this embodiment, the Zn||Cu half-cell was tested at a current density of 1 mA cm⁻¹. -2 Discharge capacity is 1mAh cm -2 Coulomb efficiency under the condition as Figure 2As shown in (d), the stable cycle is 160 times.

[0111] Figure 1 The Zn||Zn symmetric cells prepared using the electrolytes of Examples 1-12 of this invention operate at a current density of 1 mA / cm². -2 The current capacity is 1mAh cm⁻¹ -2 Cyclic performance graph under the given conditions; Figure 2 Zn||Cu batteries prepared using the electrolytes of Examples 1-12 of this invention operate at a current density of 1 mA cm⁻¹. -2 The current capacity is 1mAh cm⁻¹ -2 Cyclic performance graph under the given conditions. From Figure 1 and Figure 2 The results show that, under the same current density and discharge capacity conditions, the voltage stability of the Zn||Zn battery and Zn||Cu battery assembled with the electrolyte in Example 8 is better than that of other examples. The Zn||Zn battery assembled with the electrolyte in Example 8 still has a stable voltage after about 1800 hours of cycling, and the assembled Zn||Cu half-cell can cycle stably for 257 cycles with an average coulombic efficiency of 96.4%.

[0112] Therefore, the ZnSO4+KG0.15+DMSO10 electrolyte prepared in Example 8 of this invention is determined to be the optimal ratio.

[0113] Example 13 An aqueous zinc-ion battery electrolyte, its preparation method, and its application, comprising the following steps: (1) Weigh 2.8756g of solid ZnSO4·7H2O and add it to an empty beaker. Add deionized water to the beaker and make up to 5ml. Stir thoroughly at 25℃ until completely dissolved to obtain a ZnSO4 solution with a concentration of 2mol / L.

[0114] (2) Weigh 175.69 mg of potassium gluconate powder and add it to the ZnSO4 solution obtained in (1). Stir thoroughly at 25°C for 2 hours until completely dissolved to obtain a potassium gluconate modified electrolyte with a concentration of 0.15 mol / L, denoted as ZnSO4+KG0.15.

[0115] (3) Take 4.5 ml of the ZnSO4+KG0.15 solution obtained in (2) and add 0.5 ml of dimethyl sulfoxide solution with a pipette. Stir thoroughly at 25°C for 2 h to obtain a dimethyl sulfoxide modified electrolyte with a volume ratio of 10 v%, which is denoted as ZnSO4+KG0.15+DMSO10.

[0116] A button-type Zn||V2O5 full cell was assembled using zinc foil (30 μm thick) as the negative electrode, graphite foil loaded with V2O5 as the positive electrode, glass fiber as the separator, and the above electrolyte.

[0117] The button cell was tested using the Xinwei multi-channel battery testing system. The Zn||V₂O₅ full cell in this embodiment was cycled at a current density of 1 A / g, and the test results are as follows: Figure 3 As shown, Zn||V2O5 exhibits an excellent capacity retention of 155.59% after more than 997 cycles.

[0118] Comparative Example 1 This comparative example provides an electrolyte, its preparation method, and its application, including the following steps: Weigh 2.8756 g of solid ZnSO4·7H2O and add it to an empty beaker. Add deionized water to the beaker and bring the volume to 5 ml. Stir thoroughly at 25 °C until completely dissolved to obtain a ZnSO4 solution with a concentration of 2 mol / L, denoted as ZnSO4.

[0119] (1) Zinc foil (thickness of 30 μm) was used as the positive and negative electrodes, glass fiber was used as the separator, and the above electrolyte was added to assemble a CR2016 type button Zn||Zn symmetric battery.

[0120] The button cell was tested using the Xinwei multi-channel battery testing system. The Zn||Zn symmetric cell in this comparative example was tested at a current density of 1 mA cm⁻¹. -2 Discharge capacity is 1mAh cm -2 Cyclic performance testing under the following conditions, such as Figure 5 As shown.

[0121] (2) Zinc foil (thickness of 30μm) is used as the negative electrode, copper foil (thickness of 30μm) is used as the positive electrode, glass fiber is used as the separator, and the above electrolyte is added to assemble a CR2016 button-type Zn||Cu half cell.

[0122] The button cell was tested using the Xinwei multi-channel battery testing system. In this embodiment, the Zn||Cu half-cell was tested at a current density of 1 mA cm⁻¹. -2 Discharge capacity is 1mAh cm -2 Coulomb efficiency under the condition as Figure 5 As shown, the Coulomb efficiency drops sharply after 37 cycles.

[0123] (3) Zinc foil (thickness of 30 μm) was used as the negative electrode, graphite foil loaded with V2O5 was used as the positive electrode, glass fiber was used as the separator, and the above electrolyte was added to assemble a CR2016 type button Zn||V2O5 full cell.

[0124] The button cell was tested using the Newway multi-channel battery testing system. The Zn||V2O5 full cell in this embodiment was cycled under a current density of 1A / g.

[0125] To further investigate the effect of the electrolyte prepared in this invention on the cycle stability of the zinc anode, the cycle performance of the Zn||V2O5 battery prepared in Example 13 and Comparative Example 1 was compared. The results are as follows: Figure 3 As shown, the Zn||V₂O₅ battery prepared by adding potassium gluconate and dimethyl sulfoxide electrolyte of the present invention has better stability than the comparative example, with a capacity retention of 31.26% after 320 cycles; the cycle performance of the Zn||Zn battery prepared in Example 8 and Comparative Example 1 was compared, and the results are as follows. Figure 4 As shown, the Zn||Zn symmetric cell assembled using the electrolyte of Comparative Example 1 began to have unstable voltage after about 138 hours, while the Zn||Zn symmetric cell assembled using Example 8 still had a stable voltage after about 1800 hours, which increased the cycle life of the zinc anode by 13 times. This indicates that the presence of potassium gluconate and dimethyl sulfoxide in this invention significantly improves the long-term cycle stability of the zinc anode.

[0126] To further investigate the effect of the electrolyte prepared in this invention on the coulombic efficiency of the battery, the coulombic efficiency of the Zn||Cu battery prepared in Example 8 was compared with that of Comparative Example 1. The results are as follows: Figure 5 As shown, the Zn||Cu battery assembled with the ZnSO4+KG0.15+DMSO10 electrolyte containing additives maintained a high and stable coulombic efficiency after 257 cycles, which is higher than that of the Zn||Cu battery with the 2M ZnSO4 electrolyte. This difference is attributed to the addition of potassium gluconate and dimethyl sulfoxide additives, which facilitate uniform zinc deposition and enhance the battery's cycle stability.

[0127] To further investigate the inhibitory effect of the electrolyte prepared in this invention on the hydrogen evolution reaction (HER), this invention uses linear sweep voltammetry (LSV) to evaluate the overpotential of HER in different electrolytes. The test results are as follows: Figure 6 As shown. Clearly, at the same current density (-20 mA cm⁻¹), 2 With the addition of KG0.15+DMSO10, the overpotential increased from -1.119 V to -1.142 V, and the potential shifted negatively, exhibiting a large overpotential difference (approximately 23 mV). This indicates that the KG0.15+DMSO10 additive has a certain inhibitory effect on hydrogen evolution during the zinc plating / de-zinc process.

[0128] To more intuitively investigate the effects of the electrolytes of Example 8 and Comparative Example 1 on the morphology and products of zinc-ion batteries, this invention uses scanning electron microscopy (SEM) to observe the surface SEM images of Zn foil after immersion in the electrolytes prepared in Example 8 and Comparative Example 1 for 8 hours. The results are as follows: Figure 7 As shown, from Figure 7 As can be clearly seen, the zinc sheet soaked in the electrolyte of Comparative Example 1 developed many byproducts, while the zinc sheet soaked in the additive electrolyte of Example 8 did not show severe corrosion. This indicates that the addition of potassium gluconate and dimethyl sulfoxide additives endows the pure zinc sulfate electrolyte with a certain degree of corrosion resistance, which helps to protect the aqueous zinc ion anode.

[0129] Those skilled in the art will readily understand that the above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. An aqueous zinc-ion battery electrolyte, characterized in that, It comprises: A soluble zinc salt, a solvent and an additive; the additive is potassium gluconate and dimethyl sulfoxide, the concentration of the potassium gluconate is 0.05-0.2 mol / L, and the concentration of the dimethyl sulfoxide is 5-10 v%.

2. The aqueous zinc-ion battery electrolyte of claim 1, wherein, The concentration of the soluble zinc salt is 1-3 mol / L.

3. The aqueous zinc-ion battery electrolyte of claim 1, wherein, The soluble zinc salt is any one or more of zinc sulfate, zinc chloride, zinc acetate, zinc perchlorate, zinc nitrate and zinc trifluoromethane sulfonate.

4. The aqueous zinc-ion battery electrolyte of claim 1, wherein, The solvent is deionized water.

5. A method for preparing an aqueous zinc-ion battery electrolyte, characterized in that, It comprises the following steps: A. Adding a soluble zinc salt into deionized water and stirring to dissolve, to obtain a basic electrolyte; B. Adding potassium gluconate into the basic electrolyte and stirring to dissolve, the concentration of the potassium gluconate is 0.05-0.2 mol / L; C. Adding dimethyl sulfoxide and stirring to mix, to obtain a battery electrolyte, the concentration of the dimethyl sulfoxide is 5-10 v%.

6. An aqueous zinc-ion battery, characterized in that, It comprises a positive electrode, a negative electrode, an electrolyte and a separator arranged between the positive electrode and the negative electrode, and the electrolyte is the aqueous zinc ion battery electrolyte according to any one of claims 1-4.

7. The aqueous zinc ion battery of claim 6, wherein, The negative electrode is made of zinc or zinc alloy material.

8. The aqueous zinc ion battery of claim 6, wherein, The positive electrode is made of copper, zinc or zinc alloy material.

9. The aqueous zinc ion battery of claim 6, wherein, The positive electrode is coated with one of vanadium-based compounds, manganese-based compounds and Prussian blue-like compounds as active material on a current collector.

10. Application of the aqueous zinc ion battery electrolyte according to any one of claims 1-4 and the preparation method of the electrolyte according to claim 5 in an aqueous zinc ion battery.